Fatty Tissue Visualization 18 Hours after 133Xe Lung Ventilation Study - Bekier, A. M. (Nuklearmedizin - NuclearMedicine, 1993)
In order to check a new rebreathing unit for ventilation investigations of the lungs with radioactive gases, a 133Xe lung ventilation study was performed in a 56-year old healthy volunteer. The contamination check on the following day triggered a radiation warning caused by the retained xenon activity in the body. The whole-body scan performed 18 h after the inhalation showed clearly a faint delineation of the xenon activity, corresponding to the subcutaneous fatty tissue of the individual studied.Bei der Überprüfung einer neuen Xenon-Falle für 133Xe-Lungenventilations-untersuchungen wurde eine routinemäßige Szintigraphie bei einem 56jährigen Freiwilligen durchgeführt; sie war unauffällig. Am Tag danach zeigte die routinemäßige Kontrolle mit Hilfe eines Hand-Fuß-Monitors erhöhte Aktivitätswerte, die einen Kontaminationsalarm ausgelöst hatten. Die Ganzkörperszintigraphie 18 h nach der Inhalation zeigte trotz der tiefen Impulsrate eine klare Darstellung des subkutanen Fettgewebes, bedingt durch die 133Xe-Retention.
Keywords: 133Xe retention in the body; lung ventilation scan